Simulation of four-point beam bending test using the X-FEM method - Jakub Gontarz; Jerzy Podgórski (Budownictwo i Architektura, 2020)
This article presents the results of the computer simulations of a four-point bending test of a concrete single-edge notched beam. In this publication, the authors compared the X-FEM method of simulating the crack in the Abaqus FEA system. The paper also contains the results obtained with the Abaqus subroutine recently developed by the authors, used for defining the direction of the crack and the failure criterion. The publication explains the way of working of this algorithm. The described calculations show that computer analysis gives unrealistic results in terms of the destructive force. SEN-beam is an interesting laboratory test in which a lot of factors influence the results. It is especially important to study what phenomena occur in the final phase of the study, when the crack tip is near the opposite side.